Isolamento, caracterização e efeito citotóxico de um inibidor de tripsina isolado das folhas de Morinda citrifolia L. em linhagens de células cancerígenas humanas - Lima, Adrianne Maia (2020)
Protease inhibitors (PIs) are ubiquitous molecules capable of regulating the activity of various proteases involved in physiological and pathological processes. Several PIs with therapeutic potential against cardiovascular, inflammatory, and cancer diseases have already been reported in the literature. Recently, our research group isolated a trypsin inhibitor (here named as NLTI, Noni Leaf Trypsin Inhibitor), from Morinda citrifolia L. (noni) leaves whose biochemical characteristics and therapeutic effects are unknown. This work aimed to characterize structurally and functionally NLTI, as well as to evaluate its effects on human cancer cell lines in vitro. NLTI was purified from noni leaves by heat treatment of the protein extracts obtained and affinity chromatography (Trypsin-Sepharose 4B). Biochemical aspects of NLTI, such as its kinetic properties and stability of antitryptic activity, were investigated. The cytotoxic potential was evaluated by in vitro assays using alamarBlue reagent on the following cell lines: gastric adenocarcinoma (AGP01), tongue carcinoma (CAL-27), human melanoma (SK-MEL-103), colorectal carcinoma (HCT 116) and erythroleukemic (K-562) cell lines. Additionally, the cytotoxic effect was investigated in normal human fibroblast cell line (MRC-5). After purification steps, NLTI show a specific activity of 15 400 IU.mgP -1 , 83.74 fold purification and 0.012% yield. NLTI is a glycoprotein with an apparent molecular mass of 16 000 Da. NLTI demonstrated a mixed-type inhibition on bovine trypsin (IC50 16 x 10-9 M) with Ki of 1.69 x 10-9 M. NLTI antitrypsin activity was not lost even when the inhibitor was subjected to a wide pH range (2.0-10.0; 30 min), temperature (100 °C; 120 min) and on the presence of reducing agent (100 mM DTT; 120 min). However, in the presence of Fe3+ metal ion (10 mM; 30 min), there was a 16% reduction in its activity. NLTI (1 μM), after incubation of 72 h, was able to reduce (p <0.05) cell viability of K-562 (42.43 ± 2.34%), HCT 116 (34.84 ± 0.31%), CAL-27 (12.35 ± 0.14%) and MRC-5 (16.20 ± 0.95%). Doxorubicin (10 μM) was used as positive control. The results suggest that NLTI has cytotoxic potential and support in vivo assays, aiming to verify its future therapeutic application.